Tata Laksana Gangguan Kognitif di Layanan Primer: Tinjauan Pustaka - Arsanti, Nabila Mayori; Wreksoatmodjo, Budi Riyanto (Cermin Dunia Kedokteran, 2025)
The global elderly population continues to increase, mainly due to the increase in life expectancy. This condition may pose several problems, i.e., cognitive impairment. Cognitive impairment is a disorder characterized by impairment of cognitive ability and daily functioning, involving disturbances in thinking or memory causing a marked change from the individual’s previous level of functioning with a known or suspected cause. Cognitive impairment is classified into mild cognitive impairment (MCI) and dementia. Cognitive impairment is suspected if there is a decline in work and daily activities. Management in primary care consists of identifying and initial screening, assessments and examinations, and diagnosis. Environmental, psychological, and behavioral interventions; social involvement; nutritional management and sleep interventions; and neuropsychiatric symptom management may be applied. It is important to implement health services that focus on dementia screening and cognitive evaluation in order to prepare healthcare providers. General practitioners can refer patients with early signs or symptoms of cognitive impairment, such as problems with memory or language.